HUBUNGAN ANTARA PENGETAHUAN DENGAN MINAT MENDONORKAN DARAH DI MASA PANDEMI COVID -19 PADA PEMUDA DUSUN SENDANGSARI DESA TERONG DLINGO BANTUL TAHUN 2021 - Windadari Murni Hartini; M. Imron Mawardi; Rosalina Kuswandari; Ikhsan Bagus Khurnianto (Pusat riset dan Inovasi Nasional, 2022)
The decrease in blood donors at UTD PMI occurred during the pandemic by 30% while the need for people who needed blood increased. Youth is a group of potential donors. Based on the results of a preliminary study, 90.3% of youth in Terong Dlingo Village Bantul have never donated blood. Knowledge is closely related to the awareness of donating blood. The purpose of the study was to determine the relationship between knowledge and interest in blood donation among youth in Sendangsari Hamlet during a pandemic. The type of research used is an analytic survey with a cross sectional design. The sample technique chosen is total sampling. The results of the correlation test using the Kendall's tau-b test with a significance level of 5% there is a significant relationship between knowledge and interest in donating blood (p-value 0.006) and the correlation coefficient value of 0.314 which means it has a fairly strong close relationship. There is a significant relationship between knowledge and interest in donating blood during the pandemic in youth in Sendangsari Hamlet, Terong Kapanewon Village, Dlingo, Bantul in 2021.